THE VALUES OF ADAB IN THE INTERPERSONAL RELATIONS BETWEEN THE PROPHET MUSA AND THE PROPHET KHIDDIR AND THEIR IMPLEMENTATION IN CHARACTER EDUCATION IN TODAY'S SCHOOLS. (STUDY: QS. AL-KAHFI VERSE 66) - Rusyda Millati Hakim; Robingun Suyud El Syam; Muhtar Sofwan Hidayat (Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2026)
In the midst of increasing concerns over moral decline and challenges in character formation among students, the values of adab contained in Qur'anic narratives offer important guidance for contemporary education. This study aims to analyze the values of adab in the interpersonal relationship between Prophet Musa and Prophet Khiddir as presented in Surah Al-Kahfi verse 66 and their implementation in character education in contemporary schools. The research employed a qualitative approach using library research. Primary data were obtained from several Qur’anic commentaries, namely Tafsir Ibn Kathir, Tafsir Al-Mishbah, Tafsir Al-Qurthubi, and Tafsir Fathul Qadhir, while secondary data were collected from books, journals, scientific articles, and other relevant literature. Data collection was conducted through documentation techniques and analyzed using content analysis and the tahlili interpretation method. The findings reveal that Surah Al-Kahfi verse 66 contains important values of adab in interpersonal relations, namely humility (tawadhu’), patience, and enthusiasm for learning. The value of humility is reflected in Prophet Musa polite request to learn from Prophet Khiddir, while patience and enthusiasm for learning are demonstrated through his persistence in following the learning process. These values are highly relevant to character education in contemporary schools. Their implementation can be carried out through teachers’ role modeling, habituation of respectful attitudes toward teachers and peers, strengthening discipline and patience in learning, and creating an educational environment that supports students’ character development. Therefore, the story of Prophet Musa and Prophet Khiddir can serve as a pedagogical foundation for shaping a generation that is well-mannered, respectful, and possesses good character in both social and academic life